Re‐evaluating the distribution of cooperative breeding in birds: is it tightly linked with altriciality?. (19th April 2016) - Wang, Ning; Kimball, Rebecca T.
Abstract : The evolution of cooperative breeding (CB) in birds has aroused intensive interest for decades, largely due to the paradox that some adults forgo independent breeding to help others. While much effort has been directed at understanding the adaptive significance of CB behavior, much less effort has been spent on understanding its origin. Ligon and Burt argued that the evolution of altriciality played a key role in the origin of CB since CB occurs more frequently in altricial lineages than expected if developmental mode and CB evolved independently and that both traits arose early in the avian tree of life. We mapped presence or absence of CB, and precocial or altricial development on a recent phylogeny of all birds to re‐evaluate their conclusions. Our results suggest altriciality may be more recently derived than previously thought, and that CB species clustered in a derived land bird clade (especially within Passeriformes) where we reconstructed many gains and losses. We did find a link between cooperative breeding and altriciality. However, since CB also occurs in precocial species, has not evolved in many altricial clades, and may have evolved prior to altriciality (based on some classifications of which species have CB), it is not clear whether altriciality is linked to other factors, such as benefits to group living, that are necessary for the acquisition of CB behavior, or whether altriciality may have been a driving force in the evolution of CB itself. The relative importance of these other factors versus altriciality for the origin of CB needs to be considered.